Ditopic Chemodosimeter for Selective Detection of Nerve Agent Tabun Simulant DCNP. Issue 35 (13th September 2022) - Maurya, Chandra Kant; Pathak, Uma; Gupta, Pradeep Kumar
Abstract: Selective optical detection of highly toxic nerve agents and their mimics like diethyl cyanophosphate (DCNP) is of paramount importance for armed forces and first responders in order to decide the suitable medical countermeasures. The reported optical chemical sensors for DCNP suffered from poor selectivity due to their single point covalent interaction with analyte. To overcome this limitation, we herein, report a novel protocol utilizing a ditopic chemodosimeter which, in presence of tetrabutylammonium hydroxide (TBAOH), underwent dual interaction with reactive subunits of DCNP, viz ., electrophilic phosphorus and cyanide, to induce unique changes in its fluorescence as well as colorimetric properties. Other interfering analytes could not trigger the similar optical response in the sensing probe due to the absence of electrophilic phosphorus and cyanide. A truth table was constructed to reveal that only DCNP but not other analytes could induce changes in both fluorescence as well as colorimetric properties of sensing probe. The linearity range of the proposed method was found to be 30–70 μM while chromogenic limit of detection (LOD) was calculated to be 99 nM which are comparable to the reported methods. Thus, use of indigenously available 2‐hydroxy‐1‐naphthaldehyde as sensing probe without requiring further chemical manipulation represented a significant improvement over the literature methods for DCNP sensing. Abstract : In presence of sub‐stoichiometric amount of TBAOH, catalytic amounts of cyanide ions were generated by the hydrolysis of DCNP, which subsequently reacted with aldehyde group of sensing probe to generate cyanohydrin followed by its phosphorylation with DCNP to generate fluorescent and colored cyanohydrin diphosphate. These optical changes are collectively used for selective detection of DCNP.